PERAN PERGURUAN TINGGI TERHADAP PERKEMBANGAN EKONOMI DIDAERAH SEKITARNYA - tono, Tono Wartono (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama’ah, 2023)
Higher education institutions are expected to play a significant role in improving the economy of the surrounding areas. The purpose of this study is to analyze the role of higher education institutions in improving the economy of the surrounding areas. This study used a qualitative research method with a case study approach. Data were collected through interviews with stakeholders and document analysis. The results of this study showed that higher education institutions have a significant impact on the economy of the surrounding areas, including creating job opportunities, providing education and training for human resources, conducting research and innovation, and establishing business incubators. However, there are also some challenges that need to be addressed, such as the lack of collaboration between higher education institutions and the local government, the limited funding for research and innovation, and the difficulty in commercializing research results. Keywords: higher education institutions, economy, surrounding areas .